2020
DOI: 10.3892/ol.2020.11299
|View full text |Cite
|
Sign up to set email alerts
|

ADAM9: A novel player in vestibular schwannoma pathogenesis

Abstract: A disintegrin and metalloproteinase 9 (ADAM9) is a member of the transmembrane ADAM family. It is expressed in different types of solid cancer and promotes tumor invasiveness. To the best of our knowledge, the present study was the first to examine ADAM9 expression in vestibular schwannomas (VS) from patients with and without neurofibromatosis type 2 (NF2) and to associate the data with clinical parameters of the patients. The aim of the present study was to evaluate if ADAM9 could be used as prognostic marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…We were the first to describe ADAM9 overexpression in VS, suggesting it might be a marker for tumor growth and invasiveness [5]. However, our study was descriptive in nature and we only could speculate on ADAM9 regulation and function.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We were the first to describe ADAM9 overexpression in VS, suggesting it might be a marker for tumor growth and invasiveness [5]. However, our study was descriptive in nature and we only could speculate on ADAM9 regulation and function.…”
Section: Discussionmentioning
confidence: 86%
“…Its proteolytic activity also releases cytokines and growth factors and it modifies the ECM by interacting with integrins [4]. In previous experiments we showed an 8.8 times higher ADAM9 mRNA-expression in VS compared to healthy vestibular nerves and suggested that ADAM9 inhibition may be of significance for VS pathogenesis and potential medical treatment [5]. Furthermore, we discussed whether ADAM9 might interact with the VS cell-matrix [5].…”
Section: Introductionmentioning
confidence: 83%
“…We were the rst to describe ADAM9 overexpression in VS, suggesting it might be a marker for tumor growth and invasiveness [3]. However, our study was descriptive in nature and we only could speculate on ADAM9 regulation and function.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, we showed that a disintegrin and metalloproteinase 9 (ADAM9) mRNA-expression is 8.8 times higher in VS compared to healthy vestibular nerves and we suggested that ADAM9 inhibition may be of signi cance for VS pathogenesis and potential medical treatment [3]. Furthermore, we discussed whether ADAM9 might interact with the VS cell-matrix [3], since it is known to promote tumor invasion by such interactions [4]. In particular, this enzyme liberates membrane-bound proteins by an enzymatic modi cation called "shedding" and therefore plays a role in tumor growth and invasiveness [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PDGFC and PI3K genes were also up-regulated, both of which are involved in cell proliferation and growth [ 86 ]. Members of the metalloproteinase protein (ADAM) family are therapeutic targets in many solid tumors, ADAM9 mRNA expression is 8.8-fold higher in vestibular schwannomas compared with normal tissues, and the expression level of ADAM9 is significantly correlated with hearing loss in patients and may be a marker for judging tumor growth and invasion [ 87 ].…”
Section: Mrna In Peripheral Nervous Tumorsmentioning
confidence: 99%